Factors influencing neonatal mortality: an analysis using the Swaziland Demographic Health Survey 2007 - Eugene Zwane; Sdumo Masango (AOSIS, 2012)
This study examines the effects of socioeconomic and maternal variables on the probability of neonatal deaths. An understanding of the factors related to neonatal mortality is important in guiding the development of focused and evidence-based health interventions to prevent neonatal deaths. The data source for the analysis was the 2006-07 Swaziland Demographic and Health Survey from which survival information on 1727 infants born within the 3 years preceding the survey. Design based logistic regression incorporating survey weights was performed to analyze the associated factors. Compared to infants born at home, the odds of dying were significantly lower for infants born in a private facility (OR=0.37, 95% CI: 0.15-0.90). Neonates born in public facilities and those born at home had similar odds of dying. For newborns, whose birth size according to the mother was smaller than average, the odds of dying were more than 4 times the odds for large-sized babies (OR=4.72, 95% CI: 1.66-13.36).